Views of Medical Students Regarding Cadaver Dissections before Starting Dissections - Rajapaksa, P.; Pathirana, T.G.; Rathnayake, R.M.A.S.B.; Kumara, J.M.D.; Higgoda, E.; Heenatigala, C.; Perera, K.A.S.A.; Gallage, C.V.; Dissanayake, M.H.P.; Edirisinghe, E.A.S.T.; Yasawasdene, S.G.; Dissanayake, P.H. (Sri Lanka Medical Association, 2015)
Introduction and objectives: First year medical students are exposed to cadaver dissections (CD) as learning/teaching material and they face a variety of emotional reactions when they encounter a human cadaver for the first time. Adverse psychological effects have been reported in Western medical students (MS), with 25.2% experiencing depression and nightmares. This study was carried out to determine the views of MS regarding cadaver dissections after introduction to the dissection hall but before starting dissections proper. Method: Altogether 150 students of the 2013/2014 A/L intake to the Faculty of Medical Sciences (FMS), University of Sri Jayewardenepura (USJP) completed a simple self administered questionnaire regarding their views about CD. Results: In spite of a gender ratio of male: female of 1:2, the majority of students considered CD as challenging [80.6% (121/150)], as a stimulating way to learn [64% (96/1500] and as more informative [80% (120/150)]. After the first exposure, the majority considered CD as not a depressing task [54.5% (82/150)] and the dissection hall as a non-frightening environment [62.2% (94/150)] and onlyl4% (21/150) had recurrent thoughts of cadavers after leaving the dissection hall. The majority of the students noticed the strong formalin smell [92% (138/150)] at the entrance and 55.3% (83/150) experienced the formalin odour (after the first encounter) even while away from faculty. A high percentage 80% (120/150) stated that an interactive session with the academic staff before the CD would reduce the negative impacts and help them to gain more during the dissections. Conclusion: Although the majority of medical students are initially apprehensive towards dissections they realize the value of dissections as a learning tool. The initial adverse emotional reactions to cadaver dissections are relatively less than those documented in Western studies.
Keywords: medical students; human cadaver; formalin odour; dissections